2016
DOI: 10.1007/s00426-016-0778-x
|View full text |Cite
|
Sign up to set email alerts
|

Sharp and round shapes of seen objects have distinct influences on vowel and consonant articulation

Abstract: The shape and size-related sound symbolism phenomena assume that, for example, the vowel [i] and the consonant [t] are associated with sharp-shaped and small-sized objects, whereas [ɑ] and [m] are associated with round and large objects. It has been proposed that these phenomena are mostly based on the involvement of articulatory processes in representing shape and size properties of objects. For example, [i] might be associated with sharp and small objects, because it is produced by a specific front-close sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…Errors (i.e., the participant uttered the wrong speech unit or did not produce any response) and RTs more than two standard deviations from each participant's condition means were excluded from the reaction time analysis . It is noteworthy that a 2 SD cutoff procedure is a valid and frequently used statistical tool (Singh, ) that we have previously used in all our studies that have measured reaction times of manual and vocal responses (e.g., Tiainen, Lukavský, et al, ; Vainio, Rantala, et al, ; Vainio et al, ; Vainio, Tiainen, et al, ). Of the trials, 2% were removed as errors and 4.4% were removed as outliers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Errors (i.e., the participant uttered the wrong speech unit or did not produce any response) and RTs more than two standard deviations from each participant's condition means were excluded from the reaction time analysis . It is noteworthy that a 2 SD cutoff procedure is a valid and frequently used statistical tool (Singh, ) that we have previously used in all our studies that have measured reaction times of manual and vocal responses (e.g., Tiainen, Lukavský, et al, ; Vainio, Rantala, et al, ; Vainio et al, ; Vainio, Tiainen, et al, ). Of the trials, 2% were removed as errors and 4.4% were removed as outliers.…”
Section: Resultsmentioning
confidence: 99%
“…Gentilucci et al () found that while observing a hand grasping an object in the power grip during vocalization of the syllable [dɑ] increased the oral cavity (indicated by F1 values) as well as maximal lip aperture in comparison to observing a hand grasping an object in the precision grip, observing graspable objects alone did not modulate these parameters. In addition, Vainio, Tiainen, Tiippana, Rantala, and Vainio () found that when the participants were presented with small and large 2D shapes, and they were asked to pronounce consonant‐vowel syllables containing the vowels [i] or [ɑ] according to the shape or size of the object, the size did not produce the expected congruency effect between the vowel and the object size. However, we presume that Vainio, Tiainen, et al () did not find any influence of object size on vocal responses of the vowels [i] and [ɑ] because that study used 2D (round or spiky) shapes as stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps it would be more accurate to view them as different kinds of sound symbolism-especially to the extent that they result in different behavioural effects. There is indeed some evidence of measurable differences between different instances of sound symbolism (e.g., Vainio et al, 2016). A distinction that is often made in the crossmodal correspondence literature is between perceptual and decisional effects.…”
Section: Outstanding Issues and Future Directionsmentioning
confidence: 99%
“…These congruencies can have effects on language learning (e.g., Asano et al, 2015;Imai, Kita, Nagumo, & Okada, 2008;Perry, Perlman, & Lupyan, 2015; for a review, see Imai & Kita, 2014) and processing (e.g., Kanero, Imai, Okuda, Okada, & Matsuda, 2014;Lockwood & Tuomainen, 2015;Sučević, Savić, Popović, Styles, & Ković, 2015). Moreover, sound symbolic associations have also been shown to impact cognition more broadly, including effects on action (Parise & Pavani, 2011;Rabaglia, Maglio, Krehm, Seok, & Trope, 2016;Vainio, Schulman, Tiippana, & Vainio, 2013;Vainio, Tiainen, Tiippana, Rantala, & Vainio, 2016), memory (Lockwood, Hargoort, & Dingemanse, 2016;Nygaard, Cook, & Namy, 2009;Preziosi & Coane, 2017), and categorization (Ković, Plunkett, & Westermann, 2010;Lupyan & Casasanto, 2015; for a recent review of sound symbolism effects, see Lockwood & Dingemanse, 2015).…”
mentioning
confidence: 99%